Enhanced Psychology and Activities of Pancabudi Students with the Role of Teachers in the Time of Covid 19 - Munisa, Munisa; Nofianti, Rita; Widya, Rika; Rozana, Salma (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the role of teachers in improving the psychology and morals of class X students of Panca Budi College and to find out how to improve the morals of class X students of Panca Budi College. (3) Inhibiting factors in improving the morals of students of X Panca Budi college. This research type is strati- tative with direct observation and data retrieval at the research site and data collection techniques using observation, interviews, and documentation.